Combustion chemistry and the carbon neutral future : what will the next 25 years of research require? - Brezinsky, Kenneth (Elsevier, 2023)
As the demands for cleaner, more efficient, reduced and zero carbon emitting transportation increase, the traditional focus of Combustion Chemistry research is stretching and adapting to help provide solutions to these contemporary issues. Combustion Chemistry and the Carbon Neutral Future: What will the Next 25 Years of Research Require? presents a guide to current research in the field and an exploration of possible future steps as we move towards cleaner, greener and reduced carbon combustion chemistry. Beginning with a discussion of engine emissions and soot, the book goes on to discuss a range of alternative fuels, including hydrogen, ammonia, small alcohols and other bio-oxygenates, natural gas, syngas and synthesized hydrocarbon fuels. Methods for predicting and improving efficiency and sustainability, such as low temperature and catalytic combustion, chemical looping, supercritical fluid combustion, and diagnostic monitoring even at high pressure, are then explored. Some novel aspects of biomass derived aviation fuels and combustion synthesis are also covered. Combining the knowledge and experience of an interdisciplinary team of experts in the field, Combustion Chemistry and the Carbon Neutral Future: What will the Next 25 Years of Research Require? is an insightful guide to current and future focus areas for combustion chemistry researchers in line with the transition to greener, cleaner technologies.
Keywords: Combustion.; Clean energy.; elektronické knihy; electronic books